1994
DOI: 10.1161/01.cir.90.6.2695
|View full text |Cite
|
Sign up to set email alerts
|

Acute effects of nitrates on exercise testing in patients with syndrome X. Clinical and pathophysiological implications.

Abstract: Background Sublingual nitrates are much more effective in relieving angina pectoris in patients with coronary artery disease than in patients with syndrome X, but it is not known whether their effect on exercise tolerance is also different in these two groups of patients.Methods and Results Treadmill exercise testing was performed before and after administration of sublingual isosorbide dinitrate (ISDN, 5 mg) in 18 patients with syndrome X (effort angina and normal coronaries, group X) and in 33 patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
29
0
3

Year Published

1999
1999
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(36 citation statements)
references
References 37 publications
4
29
0
3
Order By: Relevance
“…As in a previous study [9], they demonstrated an improvement in exercise-induced ischaemia with nitrate pre-treatment in half of the stable angina patients but in only 1 of the 29 syndrome X patients. Furthermore they demonstrated a blunted coronary blood flow response to 25mcg of sublingual nitroglycerine in the cardiac syndrome X patients compared to patients with single vessel disease, when blood flow was assessed in a vessel without an epicardial stenosis and thus reflective of microvascular function.…”
Section: Advances In Nitrate Pharmacology From Coronary Microvascularsupporting
confidence: 75%
See 1 more Smart Citation
“…As in a previous study [9], they demonstrated an improvement in exercise-induced ischaemia with nitrate pre-treatment in half of the stable angina patients but in only 1 of the 29 syndrome X patients. Furthermore they demonstrated a blunted coronary blood flow response to 25mcg of sublingual nitroglycerine in the cardiac syndrome X patients compared to patients with single vessel disease, when blood flow was assessed in a vessel without an epicardial stenosis and thus reflective of microvascular function.…”
Section: Advances In Nitrate Pharmacology From Coronary Microvascularsupporting
confidence: 75%
“…In this condition, beta blockers [4], calcium channel blockers [5], nicorandil [6], enalapril [7], and trimetazidine [8] have each been shown to be effective anti-ischaemic/anti-anginal therapies in randomised clinical trials whereas nitrates have only limited benefits [9].…”
Section: Advances In Nitrate Pharmacology From Coronary Microvascularmentioning
confidence: 99%
“…• reproduction of typical pain with the dipyridamole test, usually with typical ischemic changes but no myocardial contraction abnormality 3 ; • worsening of exercise test result after sublingual nitrates, 4 consistent with the frequent clinical report of a poor response to sublingual nitrates; • ischemic myocardial metabolic changes by magnetic resonance spectroscopy 5 ; and • release of lipid peroxidation products in the coronary sinus at the end of pacing-induced ischemic changes. 6 The causes of this coronary microvascular dysfunction may be multiple, as suggested by the total absence of iobenguane 123 I sulfate cardiac uptake in Ͼ50% of the cases, by a regional defect corresponding to the site of thallium defects in about 25%, and by totally normal uptake in the remaining 25%.…”
supporting
confidence: 55%
“…might be different in the two compartments of coronary circulation, 25,26 thus also conditioning the effectiveness of treatment on the two forms of angina.…”
mentioning
confidence: 99%